Orofacial manifestations in outpatients with anorexia nervosa and bulimia nervosa focusing on the vomiting behavior - Lourenço, M (2017)
Objective: This case-control study aims to evaluate the oral health status and orofacial problems in a group of outpatients with eating disorders (ED)—either anorexia nervosa (AN) or bulimia nervosa (BN)—further focusing on the influence of vomit. Materials and methods: Fifty-five women outpatients with AN or BN diagnosis were invited to participate, of which 33 agreed. ED outpatients and matched controls were submitted to a questionnaire and clinical oral examination. Results: Multivariate analysis identified a significantly higher incidence of teeth-related complications (i.e., tooth decay, dental erosion, and self-reported dentin hypersensitivity), periodontal disease, salivary alterations (i.e., hyposalivation and xerostomia), and oral mucosa-related complications in ED outpatients. Dental erosion, self-reported dentin hypersensitivity, hyposalivation, xerostomia, and angular cheilitis were found to be highly correlated with the vomiting behavior. Conclusions: ED outpatients were found to present a higher incidence of oral-related complications and an inferior oral health status, compared to gender- and age-matched controls. Alterations verified within outpatients were acknowledged to be quite similar to those previously reported within inpatients, in both of nature and severity, thus sustaining that the cranio-maxillofacial region is significantly affected by ED, even in the early/milder forms of the condition, as expectedly verified within outpatients.